Delaying reclosure of bladder exstrophy leads to gradual decline in bladder capacity. Issue 3 (June 2020) - Wu, Wayland J.; Maruf, Mahir; Harris, Kelly T.; Manyevitch, Roni; Patel, Hiten D.; Di Carlo, Heather N.; Gearhart, John P.
Summary: Introduction: After unsuccessful repair of bladder exstrophy, when to repeat surgical intervention is unclear. One must balance time required for tissue healing with the damaging effects of an exposed urothelium to the environment. Objective: The authors aim to study whether a relationship exists between bladder growth/capacity and time till eventual successful closure. Study design: An institutional database of exstrophy-epispadias complex patients was queried for failed exstrophy closure with successful repeat reconstruction, at least three consecutive bladder capacity measurements, and measurements obtained at least three months following successful closure. Patients closed successfully in the neonatal period were used as a comparative group. Linear mixed effects models were used to study the effect of time and age on bladder capacity. Results: Forty-seven patients requiring reclosure and 117 who had successful neonatal closures were included. Two models were created. The first linear mixed effects model found that for a given age, the bladder capacity declined approximately 9.6 mL per year (p = 0.016). The second model found that when time to successful closure was grouped by quartiles, compared to neonates, those in the fourth quartile had significantly decreased bladder capacity of 28.8 cc (p = 0.042). An interaction model comparing neonates and those requiring reclosure did not demonstrate a significant change in bladder growth rate (p = 0.098). A model stratified by quartiles similarly did not find any significant impact to bladder growth rate. Discussion: From the general linear mixed effects models, the authors conclude when compared to neonates, (1) there was an approximate 9.6 cc loss of total bladder capacity per year taken until successful closure, and that (2) those who were delayed the longest had the most significant difference in bladder capacity. This study required stricter inclusion criteria compared to previous publications, and therefore the conclusions that can be drawn regarding bladder growth rates may be more reliable. Future studies will examine the effects of delayed closure on the bladder at the cellular level. Conclusions: There is a demonstrable significant impact on overall bladder capacity with increasing delay to successful reclosure. One should be cautious when prolonging reconstruction of the bladder as these data demonstrate a time dependent decline in overall capacity. Summary Figure Linear mixed effect model demonstrating predicted bladder capacity for a given age. Significant difference was seen between the fourth quartile group (BCap4, red line) compared to neonatal closure (BCapn, blue line). ( Abbreviations: BCap, bladder capacity. ) (For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article). Summary Figure